Micronutrient Intervention In The Preconception Period: Literature Review - Aidil Akbar; Rinova Dinda Amelya Lubis; Seintya Gimi Lestari (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Micronutrient intervention in the preconception period is an important strategy in improving maternal and child health as a whole. The pre-pregnancy period is a critical phase that affects the success of the pregnancy process and fetal growth. This study aims to systematically review various scientific findings regarding the impact of preconception micronutrient supplementation on maternal nutritional status, pregnancy outcomes, and child development. The method used is in the form of literature reviews of reputable international articles published between 2021 and 2025. A search was conducted for several articles, and 10 of them were selected based on inclusion criteria such as a focus on preconception interventions, available in full text, and from globally indexed journals. The results of the study showed that micronutrient supplementation such as iron, folic acid, and multivitamins can reduce the risk of premature birth and low birth weight babies, as well as improve children's cognitive abilities. Primary service-based interventions and communication technology are considered to be able to reach women of childbearing age effectively. However, low public awareness of the importance of preconception nutrition is still an obstacle in the implementation of the program. This study recommends the integration of preconception nutrition policies in the national health system in a sustainable manner.